(untitled) (Applied Biological Research, 2015)
Tuta absoluta has recently become one of the most devastating pests of tomato in Egypt. In this study, field experiments were conducted during two summer seasons (2012 and 2013) to determine the effectiveness of four insecticides, abamectin 152.4 g L-1 + thiamethoxam 33.2 g L-1 (Agriflex 18.6% SC), chlorpyrifos (Lirifos 48% EC), spinosad (Tracer 24% SC) and imidacloprid (Admire 20% SC), in controlling T. absoluta in tomato. These insecticides were found effective in reducing T. absoluta infestation in both the seasons. Spinosad proved most promising and caused 98.6% reduction in T. absoluta infestation in comparison of 62.8 and 54.8% by abamectin + thiamethoxam and chlorpyrifos, respectively. Imidacloprid was least effective with infestation reductions of 9.3%.